Effect of sources and doses of acidifiers on pH of soil collected from floor of chicken housing facilities - Deus, Angélica Cristina Fernandes [UNESP]; Motta, Antônio Carlos Vargas; Gugelmin, Eduardo Kieras; Dal Pizzol, Rodrigo; Malinoski, Simone; de Oliveira, Cibelle Tamiris (My University, 2023)
Acidification of animal manure has been one of the approaches used to combat the proliferation of bacteria and high volatilization of ammonia (NH3). Conversely, alkalinization is performed with basic oxides in Brazil, which raises the pH of the litter and soil from floors of chicken facility, creating a constant source of contamination in them. In this context, this study was undertaken to examine the effect of sodium bisulfate (SB) and elemental sulfur (ES) on the acidification of different soils from floor of chicken housing facilities, considering their efficiency and reaction time. The experiment involved tree soils collected inside chicken facilities (at six, 36, and 60 months of occupation), as well as soil that was collected outside the facilities, totaling four sampling sites. Both acidifier sources-SB and ES-were applied at six increasing doses (0, 2, 3, 6, 12, and 24 cmolc kg-1 of H+ in the 3-cm soil layer), and incubated for up to 53 days. At the end of each incubation period, the pH of the soil was measured. The results suggest that SB is efficient in reducing the pH of chicken soil, with an immediate reaction occurring after its application. Under the conditions adopted in the present study, the recommended dose of SB to reduce the pH to 5.0 was 6 cmolc kg-1 of H+, which corresponded to the application of 7.2 g of the product in 500 g of soil. Elemental sulfur showed a slow reaction and low efficiency. The use of SB quickly and efficiently provides the acidification of soil from floor of chicken housing facilities.
Efeito de fontes e doses de acidificantes no pH do solo coletado do piso de galinheiros
Keywords: Acidification; Broiler production; Chicken litter; Poultry house management